Book Review - eLearnings: Implementing a national strategy for ICT in education, 1998-2010 - Darren Sudlow (Flexible Learning Association of New Zealand, 2013)
In 2010 Core Education released a book entitled, Elearnings: Implementing a national strategy for ICT in Education, 1998-2010 which outlines the journey various stakeholders have been on during that period. This review examines the value of the book for a teacher working in a fully online or 'blended' context.